The Semantics of the Spanish Adjective Positions: a Matter of Focus - Dam, Lotte (Research in Language, 2018)
This paper presents a hypothesis about Spanish adjective position that accounts for different occurrences in language use. The hypothesis is based on the idea that the modifier position itself is a meaningful sign and that the meaning of the modifier position is related to focus: the postnominal modifier creates focus, whereas the prenominal modifier does not create focus. Drawing on the analysis of examples from a text corpus, the paper suggests that the proposed meaning of the two positions offers an account of various empirical phenomena. For example, it can explain why some adjectives are normally placed in one of the positions and why some adjectives change meaning according to their position.